Compensatory Class III malocclusion treatment associated with mandibular canine extractions - Janson,Guilherme (2017)
ABSTRACT Skeletal Class III malocclusions are ideally treated with orthodontic-surgical approaches. However, if there are no significant soft tissue implications and the patient does not want to undergo orthognatic surgery, other treatment options may be considered. The current case report describes a compensatory alternative for Class III malocclusion treatment, by means of mandibular canine extractions. This treatment alternative provided facial profile and occlusal improvement, which remains stable seven years posttreatment.